Multiplex PCR assay for detection of human interferon alpha2b gene in transgenic plants - Gerasymenko, I.M.; Sakhno, L.O.; Mazur, M.G.; Sheludko, Y.V. (Цитология и генетика, 2012)
During the last decade interferons are regarded as potent candidates for generation of plant-based edible vaccines because of broad spectrum of antiviral activities and adjuvant properties. Establishment and certification of numerous interferon producing plant systems requests development of fast and efficient multiplex PCR protocol for the transgene detection in GM plants. Here we represent a protocol for simultaneous amplification in one assay of fragments of hIFN alpha 2b gene and two control genes, namely virD1 of Agrobacterium tumefaciens and conservative region of plant actin gene.